Antiinflammatory effects of salmeterol/fluticasone propionate in chronic obstructive lung disease. - Barnes, N; Qiu, Y; Pavord, I; Parker, D; Davis, P; Zhu, J; Johnson, M; Thomson, N; Jeffery, P (2006)
RATIONALE: No currently available treatment is reported to reduce the exaggerated airway wall inflammation of chronic obstructive pulmonary disease. OBJECTIVES: We tested the hypothesis that inhaled combined long-acting beta2-agonist (salmeterol) and corticosteroid (fluticasone propionate) will reduce inflammation. METHODS: Bronchial biopsies and induced sputum were taken from 140 current and former smokers (mean age, 64 yr) with moderate to severe disease, randomized in a 13-wk double-blind study to placebo (n = 73) or salmeterol/fluticasone propionate 50/500 microg (n = 67) twice daily. Biopsies were repeated at 12 wk and sputa at 8 and 13 wk. After adjustment for multiplicity, comparisons between active and placebo were made for median change from baseline in the numbers of biopsy CD8+ and CD68+ cells/mm2 and sputum neutrophils. MEASUREMENTS AND MAIN RESULTS: Combination therapy was associated with a reduction in biopsy CD8+ cells of -118 cells/mm2 (95% confidence interval [CI], -209 to -42; p = 0.02), a reduction of 36% over placebo (p = 0.001). CD68+ cells were unaffected by combination treatment. Sputum differential (but not total) neutrophils reduced progressively and, at Week 13, significantly with combination treatment (median treatment difference, 8.5%; 95% CI, 1.75%-15.25%; p = 0.04). The combination also significantly reduced biopsy CD45+ and CD4+ cells and cells expressing genes for tumor necrosis factor-alpha and IFN-gamma and sputum total eosinophils (all p < or = 0.03). These antiinflammatory effects were accompanied by a 173-ml (95% CI, 104-242; p < 0.001) improvement in prebronchodilator FEV1. CONCLUSIONS: The combination of salmeterol and fluticasone propionate has a broad spectrum of antiinflammatory effects in both current and former smokers with chronic obstructive pulmonary disease, which may contribute to clinical efficacy.